A genre-based analysis of hotel advertisements in Malaysia / Li Yong Qing - Li, Yong Qing (2013)
This is a genre-based study on hotel advertisements in Malaysia. The purpose of the study is to use a genre approach to explain the use of advertising language in Malaysia hotel advertisements in attaining their objectives. The study also examines the way the advertisements were written. The Five-Move structure for hotel advertisements proposed by Gu Xiangfen (2008) has been adopted to analyze a sample of 20 Malaysia hotel advertisements. The study also looks into other aspects of the texts, such as the communicative purposes and the linguistic features. Findings from quantitative analysis indicate the following: First, Malaysia hotel advertisements serve as a communicative medium to persuade potential customers to buy their products or services, provide information portals for potential customers on hotel information and act as a marketing instrument to promote good images and services of hotels. Second, the Five-Move structure is found to be suitable for investigating the structure of Malaysia hotel advertisements. Only Move 4 “Internal Philosophy and Guidelines” is not significant in the data. The rhetorical moves of Malaysia hotel advertisements includes Identifying Service (Brand Name and Highlighting), Establishing Credentials (Location and Offering Rating/ Awards & Accolades), Introducing Service & Facilities (Rooms & Services, Function rooms & Facilities and Dining & Bar) and Providing Contact. The Optional Moves or Steps are Expressing General Greetings and Invitation, Background Description and Internal Philosophy & Guidelines. Third, the most common linguistic features are identified in the samples. They are the pronoun „you‟ and „your‟, Adjectives, Binomial and Multinomial Expressions, Nominal, Ellipsis and Imperatives. The findings also indicate that some other non-linguistic features are used in the samples, such as colorful and attractive pictures, logos and explicit promotional sub-headings. In all, the findings of this study enrich the promotional genre colony put forward by Bhatia (1993) and add on to the literature in this field for researchers as well as materials for teaching and learning of practical English writing in the field of ESP.